Comunidades de práticas: da informalidade do saber matemático no cultivo do Passiflora Edulis ao saber matemático formal escolar - ARAÚJO, Danillo Nascimento (2023)
This Course Completion Work (TCC) is the result of a research that aimed to analyze the mathematical knowledge used by farmers in their informal practices, more specifically in passion fruit cultivation, seeking to bring the informal knowledge produced by them closer to the formal knowledge school aiming to highlight the importance of these two types of knowledge in the construction of the student's mathematical knowledge. The research was characterized, regarding its approach, as qualitative; As for the objectives, it was exploratory in nature, and as it was carried out with two farmers (Seu Júlio and Seu Nicolas), residents of the São Pedro do Caratateua community located in the municipality of Aurora do Pará/PA, it was characterized as a case study. The theoretical basis of the research was carried out in a bibliographical way on the Ethnomathematics Program, which served as a subsidy to investigate the mathematical knowledge of farmers, as well as to relate them to school knowledge. In order to obtain the necessary information for the investigation of the research, interviews were carried out with the farmers, and some parts of the passion fruit cultivation process were also observed, in order to report all the details of this planting. The results of this research showed that even a farmer, who many times has never gone through a school processor, manages to produce his own mathematical knowledge, acquired from his needs and experiences throughout his life, which are passed on in generations and the importance to make an approximation of this informal mathematical knowledge to formal mathematical knowledge, emphasizing that this approximation can propose a better teaching-learning process.